IMPLEMENTASI KEBIJAKAN KAWASAN TERBATAS MEROKOK (KTM) DI FAKULTAS ILMU SOSIAL DAN ILMU POLITIK (FISIP) UNIVERSITAS DIPONEGORO KOTA SEMARANG - Devi, Elok Tamara; Rahman, Amni Zarkasyi (Journal of Public Policy and Management Review, 2017)
Faculty of Social and Political Science Diponegoro University has stipulated Restricted Smoking Area policy to cope with negative effects of cigarette, but it is not effectively applied. Researcher has found that it has yet to be optimally implemented and many violations occured. The objective of the research is to describe and analyze the implementation of Restricted Smoking Area policy (KTM), as well as to find out supporting and inhibiting factor of the implementation. This research was conducted in qualitative approach with descriptive type. Data was collected from observation, interview, and documentation. Based on the research, it shows that implementation of Restricted Smoking Area policy has not been optimally implemented, caused by all existing factors such as communication, resource, birocration structure, and disposition become an obstacle for the implementation of Restricted Smoking Area policy in Faculty of Social and Political Science Diponegoro University.